Reassessing effective protection rates in a trade in tasks perspective: Evolution of trade policy in factory Asia - Antonia Diakantoni; Hubert Escaith (World Trade Organization (WTO), 2012)
With international trade moving from trade in (final) goods to trade in tasks, effective protection rates (EPRs) are back to the stage, allowing us to measure the overall protection of a product or sector by including the production structure and the origin of the inputs -domestic or imported. Input-output matrices are used in this paper to monitor the production structure of 10 Asian-Pacific countries between 1995 and 2005, and to calculate sectorial EPRs. The paper proposes a series of counter-factual simulation methods aimed at isolating the specific contribution of changes in tariff policies, in production structure or in real exchange rates. Working on international input-output matrices allowed also to compute and compare the average propagation length of a cost-push linked to a sudden change in tariff duties, identifying those sectors that are the most deeply interconnected, both in the intensity and in the length of their inter-industrial foreign relationships.
Keywords: F13; F23; 330; Tariff; Effective Protection; Trade in Value Added; International Outsourcing; Asian Input-Output; Effektive Protektion; Input-Output; Produktionsstruktur; Internationale Produktion; Outsourcing; Asiatisch-pazifischer Raum